2020
DOI: 10.21608/jnsbu.2020.159439
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dysfunction in Women with Diabetes: Counseling intervention

Abstract: Background: Sexual dysfunction is common gynecological complaint among diabetic women due to its complication effect on sexual function. Aim of this study: Examine the effect of counseling session on female sexual dysfunction regarding diabetic female. Research design: A quasi-experimental design was utilized to carry out this study. Sample: A purposive sample of 132 diabetic women who had sexual dysfunction was recruited in this study. Setting: The study was carried out at six October University Hospital whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Moreover, regarding the number of living children more than half of them have one to three children and most of them are cesarian. These results agreed with Gerges et al (10) who studied sexual dysfunction in women with diabetes in Banha and revealed that more than two-thirds of the studied women had from one to three children, in contrast to the result of the current study more than two-thirds of them were delivered with Vaginal delivery mode.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, regarding the number of living children more than half of them have one to three children and most of them are cesarian. These results agreed with Gerges et al (10) who studied sexual dysfunction in women with diabetes in Banha and revealed that more than two-thirds of the studied women had from one to three children, in contrast to the result of the current study more than two-thirds of them were delivered with Vaginal delivery mode.…”
Section: Discussionsupporting
confidence: 93%
“…This tool was developed by [ 12 ] to assess female sexual function. This scale consists of 19 items that are divided into 6 domains: [ 1 ] Desire 2 items [ 2 ], arousal 4 items [ 3 ], lubrication 4 items [ 4 ], orgasm 3 items [ 5 ], satisfaction 3 items and [ 6 ] pain 3 items. each domain was rated on a scale of 0 or 1–5 score, 0 indicates that the subject reports (having no sexual activity), 1 indicates (almost having no sexual activity), 2 indicates (a few times having sexual activity), 3 indicates (sometimes having sexual activity), 4 indicate (almost times having sexual activity) score 5 (suggestive of normal sexual activity).…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of diabetes has risen significantly by 62% over the last ten years [ 3 ]. The International Diabetes Federation (IDF) listed Egypt among the world’s top 10 countries in the number of patients with diabetes [ 4 ] In Egypt, the prevalence of diabetes is around 15.56% among adults between 20 and 79 years of age, with an annual death of 86,478 related to diabetes [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation